Product Market Deregulation and Growth : New Country-Industry-Level Evidence - Bouis, Romain (IMF Working Papers; Working Paper ;, 2016)
The paper investigates the economic effects of major product market reforms in some of the historically most protected non-manufacturing industries. It relies on a unique mapping between new annual data on reform shocks and sector-level outcomes for five network industries (electricity and gas, land transport, air transport, postal services, and telecommunications) in twenty-six countries spanning over three decades. The use of a threedimensional panel and careful instrumentation of reform shocks using external instruments enables us to control for economy-wide macroeconomic shocks and address possible sources of omitted variable bias more broadly. Using a local projection method, we find that major reductions in barriers to entry yield large increases in output and labor productivity over a five-year horizon, concomitant with a relative price decline. By contrast, there is only a weak positive effect on sectoral employment, and investment is essentially unaffected, suggesting that output gains from reform primarily reflect higher total factor productivity. It takes some time for these gains to materialize: effects become statistically significant two to three years after the reform, as prices start dropping, and productivity and output increase significantly. However, there is no evidence of any negative short-term cost from reform, including under weak macroeconomic conditions. These findings provide a clear case for intensifying product market reform efforts in advanced economies at the current juncture of weak growth.